Corporate Criminal Responsibility for the Crime of Mixing LPG in the Perspective of Consumer Protection and Law Enforcement - Situmeang, Sahat Maruli Tua (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to find out how the criminal responsibility of agents of mixed 3-kilogram LPG gas is in the perspective of consumer protection and to find out what aspects encourage the misuse of LPG gas by mixing mode. The research method used is normative juridical and by using a statutory approach. The results of the study show that agents can be held accountable for their mistakes, namely misusing LPG cylinders and their contents where this is detrimental to society as consumers as stipulated in Law Number 22 of 2001 concerning Oil and Gas in conjunction with Article 55 of the Criminal Code through vicarious liability .The aspect that encourages the misuse of 3-kilogram LPG gas is due to social inequality, especially in the economic sector, which is then exacerbated by the condition of the subsidy policy that is not on target as a factor in the occurrence of crime. Based on this, it shows that the low quality of law enforcement is passive and the lack of supervision of the distribution of subsidized LPG gas, therefore it is important to change the subsidy system and increase supervision of the distribution of subsidized LPG gas through evaluating the distribution of subsidized LPG gas to the community so that it is right on target and prevents any victims of LPG gas abuse.